2002
DOI: 10.1097/00006534-200205000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Epigastric Skin Flap Survival by Adenovirus-Mediated VEGF Gene Therapy

Abstract: A novel approach to treat ischemic tissues by using gene therapy has recently been introduced on the basis of the angiogenic potential of certain growth factors. The authors investigated the effect of adenovirus-mediated gene therapy with vascular endothelial growth factor (VEGF) delivered into the subdermal space to treat compromised skin flaps. For this purpose, the epigastric skin flap model in rats, based solely on the right inferior epigastric vessels, was used. Thirty male Sprague-Dawley rats were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 35 publications
0
77
0
Order By: Relevance
“…From a surgical point of view an intraoperative application would be most desirable but angiogenesis and improved perfusion as a consequence will need time to develop. Most previous studies demonstrated increased flap survival, but failed to show evidence of increased VEGF expression, increased flap perfusion or improved angiogenesis [9,24,25]. We show that the delivery of AdVEGF 165 to the preoperative flap site 3 or 7 days before surgery indeed leads to increased VEGF concentration in the skin, increased perfusion of the injected area, and an increased flap survival size together with a reduced necrosis.…”
Section: Introductionmentioning
confidence: 53%
“…From a surgical point of view an intraoperative application would be most desirable but angiogenesis and improved perfusion as a consequence will need time to develop. Most previous studies demonstrated increased flap survival, but failed to show evidence of increased VEGF expression, increased flap perfusion or improved angiogenesis [9,24,25]. We show that the delivery of AdVEGF 165 to the preoperative flap site 3 or 7 days before surgery indeed leads to increased VEGF concentration in the skin, increased perfusion of the injected area, and an increased flap survival size together with a reduced necrosis.…”
Section: Introductionmentioning
confidence: 53%
“…Experimental evidence indicates that VEGF-165 gene therapy is feasible in augmenting skin flap viability. Specifically, local subdermal or subcutaneous injection of liposomal or adenoviral vectors encoding the cDNA of VEGF-165 at 0.5, 2, 3, 7, or 14 days before surgery effectively augmented skin flap viability in the rat, but the mechanism was not studied (9,11,20,21). Local subcutaneous injection of VEGF-165 plasmid DNA 7 days preoperatively also increased skin viability in rat musculocutaneous flaps, and again the mechanism was not studied (49).…”
mentioning
confidence: 98%
“…In order to prevent complications like this, several studies have been done to achieve better neovascularization during flap prefabricating process, such as the application of angiogenic cytokines vascular endothelial growth factor (VEGF) (Li et al 2000), basic fibroblast growth factor (bFGF) (Bayati et al 1998), and transforming growth factor (TGF)-β (Iwasawa 1993), or the administration of gene therapy (Lubiatowski et al 2002). However, neither the local application of angiogenic cytokines nor the administration of gene therapy can be effective long-term without obvious side effects.…”
mentioning
confidence: 99%